Perilaku Remaja Mencoba Merokok: Peran Iklan Rokok, Teman Sebaya dan Orang Tua - Ervi Rachma Dewi; Widodo Bagus Waldiani; Muhamad Husni Mubaroq; Maria Ulfa; Eny Pujiati (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
The Global Youth Tobacco Survey (GYTS) data shows an increase in the prevalence of smokers aged 13 to 15 years from 18.3% (2014) to 19.2% (2019). In Demak Regency, according to data from the Demak Regency Health Office, the number of smokers over the past three years has decreased, with a decrease from 45% (2021) to 43% (2022) and then to 42% (2023). Among smokers aged 15-18 years, the rate dropped from 8.77% (2022) to 4.06% (2023). This study aims to explore the influence of cigarette advertising, peer influence, and parental influence on adolescents who experiment with smoking at SMP Negeri 1 Demak. This study used a cross-sectional method with a sample of male adolescents at SMP Negeri 1 Demak. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using univariate and bivariate tests to examine the relationships between variables. The results showed that cigarette advertising played a role in adolescent smoking behavior with a p value of 0.001. Peers have no role in adolescent smoking behavior with a p value of 0.103, and the role of parents has a role in adolescent smoking behavior (p value 0.001). This study reveals that the role of cigarette advertising and parents play a role in adolescent smoking behavior while the role of peers has no effect on adolescent smoking behavior.